Modification of p53 protein profile by gamma irradiation followed by methyl donor starvation - Batra, Vipen; Kesavan, Vellappan; Mishra, Kaushala P. (Molecular and cellular biochemistry, 2006)
The possible beneficial radio-protective effects of one-carbon transfer agents namely folate, choline and methionine have been the subject of extensive investigation. Ionizing radiation is known to extensively damage the DNA. One-carbon transfer agents have been proposed to have important role in context of DNA repair via their role in purine and thymidylate synthesis and in DNA methylation. Sufficient dietary availability of one-carbon transfer agents therefore, might have ability to modify radiation effects. In present study modifications in level of tumor suppressor protein p53 by gamma irradiation followed by methyl donor starvation was observed. Experiments showed an increase in nuclear and cytoplasmic p53 protein concentration in liver, spleen and thymus. The overall rise in the level of p53 protein in liver was found to be less than that in spleen and thymus. Moreover significant heterogeneity in the basal level of expression of the p53 protein in liver, spleen and thymus was observed as the level of p53 protein in spleen and thymus was found to be 7-8 fold more than that in liver. Results indicated that radiation stress followed by methyl donor starvation could significantly induce p53 protein in spleen and thymus where there was a dramatic accumulation of p53 following irradiation, while in other tissues, particularly the liver, no such dramatic response was seen. Folate contribution of intestinal bacteria was found to influence p53 protein levels. Our observations indicated a prominent role played by the methyl donors in protecting the cell against harmful effects of ionizing radiation.